2010
DOI: 10.3748/wjg.v16.i48.6104
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism of MRP1 associated with reduced survival in hepatocellular carcinoma

Abstract: the MRP1 -1666GG genotype predicted a worse outcome and was an independent predictor of poor survival in patients with HCC from Southeast China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Previous reports suggested that a functional polymorphism in codon 72 of p53 gene, which encodes polyproline domain with a vital role in apoptosis induction, is in relation to the most cancers (18)(19)(20)(21)(22)(23) and prevalence of exon 5-8 mutations, which encodes the DNA binding domain of the TP53 molecule are found in many of human cancers (5,26). On the other hand, a report by Zhao et al, indicated that promoter polymorphism of ABCC1 gene too, is associated with cancer development (10). Here, polymorphisms of 72 and 282 codons of p53 gene and promoter of ABCC1 were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports suggested that a functional polymorphism in codon 72 of p53 gene, which encodes polyproline domain with a vital role in apoptosis induction, is in relation to the most cancers (18)(19)(20)(21)(22)(23) and prevalence of exon 5-8 mutations, which encodes the DNA binding domain of the TP53 molecule are found in many of human cancers (5,26). On the other hand, a report by Zhao et al, indicated that promoter polymorphism of ABCC1 gene too, is associated with cancer development (10). Here, polymorphisms of 72 and 282 codons of p53 gene and promoter of ABCC1 were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences indicated that SNPs within the ABCC1 (MRP1) are important in predicting the response to chemotherapy in different cancers. This gene can induce a characteristic mutation in p53 (10,30). Previous studies have shown that p53 mutations are significantly associated with a poor prognosis for patients with cancer (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literatürde, bu proteini kodlayan gendeki polimorfizmlerin, protein ifadesini değiştirdiğini gösteren çalışmalar da bulunmaktadır (17). Bununla birlikte, mrP1'i kodlayan genlerdeki polimorfizmlerin idrar arsenik düzeylerine etkisini Türk populasyonunda araştıran bir çalışmaya literatür taramalarında rastlanmamıştır.…”
Section: Introductionunclassified